On The Main Issues Of Implementing The Institute Of Citizens’ Legislative Initiative - Hakobyan, Ruzanna; Hakobyan, Hranush (Bulletin of Yerevan University C: Jurisprudence, 2025)
The article is devoted to the issues of implementing the institute of citizens’ legislative initiative. As a result of the constitutional amendments of 2015, a new institute of direct or immediate implementation of democratic power was adopted in the Republic of Armenia, the implementation of which is fraught with serious legislative and organizational problems and imperfections. The article examines the peculiarities of the institution of citizens’ legislative initiative in the Republic of Armenia and other countries using the method of comparative legal analysis. The aim of the article is to analyze the key issues of proposing a draft law by citizens with the right to vote through a civil initiative, and the objective is to reveal the importance of citizens’ legislative initiative and the difficulties of its implementation using the example of the Republic of Armenia and other states. The theoretical basis of the article is scientific works related to the topic, and the normative legal basis is the Constitutions of the Republic of Armenia and other states, as well as relevant legislative acts. As a result of the study, it is proposed to review the number of citizens exercising the right of legislative initiative, the number of signatures required to identify citizens for holding a referendum on the same issue and for demanding a referendum in general, and other issues. The article is topical and contains scientific novelty, related to the proposals for constitutional amendments in the Republic of Armenia on how to clarify and improve the normative legal foundations of the institution of civic initiative aimed at strengthening direct democratic power.